Morphological changes of descending testes during postnatal developmental stages in the Rabbit (Oryctolagus cuniculus) - Ismail, Ammar; Atyia, Mahdi Abdul kareem (The Iraqi Journal of Veterinary Medicine, 2013)
This study was conducted to elucidate the morphological changes of the testis of the domestic rabbit (Oryctolagus cuniculus) during the postnatal life. The animals were divided in to seven age groups, eight animals for each group. The age of these groups were (1, 15, 30, 60, 90, 120, and 150 days). The mean weights, volume, length, width, and thickness of both left and right testes wererecorded. The positions of testes in all ages were described. The results showed the testes were found at sub lumber region at one day postnatally, moved and start ingress the inguinal canal at 15 days of age, and mostly located moving in the inguinal canals and near to the developing scrotum between 30 and 60 days. This become completely within the scrotum at 90 days. The testes weight showedsharply increasing at 15 days. Then continued grew gradually, until 90 days of age when the greatest growth rate. After 90 days of life the testicular weight show slower rate of growing to reach adult weight at 150 days.